PENDAMPINGAN PERSIAPAN KOMPETISI SAINS MADRASAH (KSM): MENJAWAB TANTANGAN INTEGRASI ALQUR’AN DAN SAINS DALAM SOAL KSM - Zamista, Adelia Alfama; Deswita, Pipi (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2024)
The madrasa science competition (KSM) is a science competition for students organized by the Ministry of Religion. KSM has the characteristics of science questions that are integrated with religious values. However, the students who will compete in the KSM are not familiar yet with the questions that combine science and religion. Based on this, a service was carried out in the form of assistance in the preparation of KSM for students participating in KSM in Pesisir Selatan Regency. This activity aims to make students accustomed and able to work on KSM questions that integrate general and religious knowledge. The trial activities are carried out classically with a realistic mathematical approach and a contextual approach. Brainstorming method is used during the practice. The result of this mentoring activity for prospective KSM participants at the provincial level is an increase in participants’ motivation as well as an increase in the ability of participants to work on integrated Physics questions at KSM.